Micro‐Raman spectroscopy identifies crocidolite and erionite fibers in tissue sections1. (29th April 2013) - Croce, Alessandro; Musa, Maya; Allegrina, Mario; Rinaudo, Caterina; Baris, Y. Izzettin; Dogan, A. Umran; Powers, Amy; Rivera, Zeyana; Bertino, Pietro; Yang, Haining; Gaudino, Giovanni; Carbone, Michele
Abstract : Exposure to asbestos or erionite is associated with malignant mesothelioma (MM) and other diseases. Micro‐Raman spectroscopy and Variable Pressure Scanning Electron Microscopy/Energy Dispersive Spectroscopy were used to identify mineral fibers in histological sections of various tissues taken from mice injected with crocidolite asbestos and erionite fibers. Routine diagnostic histopathological slides of biopsies from erionite‐exposed MM patients from Turkey were also analyzed. We show here that micro‐Raman spectroscopy easily permits the recording of distinct Raman patterns of both crocidolite and erionite fibers, in both murine tissues and in human biopsies. The described findings provide a new powerful and non‐destructive tool to determine the type of fiber exposure in patients with MM and other mineral fiber‐associated diseases. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : Micro‐Raman Spectroscopy and Scanning Electron Microscopy were applied to identify fibers on histological sections from different tissues of mice injected with crocidolite asbestos or erionite. Also, sections prepared for medical diagnosis from lung biopsies of patients affected by malignant mesothelioma from Cappadocia were analyzed. Micro‐Raman spectroscopy is proved as technique allowing an easy and sure identification of crocidolite and erionite, both in mice tissues and in human biopsies.